Tariff policy towards a monopolist in the presence of persuasive advertising - Leahy, Dermot (Economic & Social Studies, 1992)
This paper considers the positive and normative aspects of tariffs and advertising taxes in a situation in which a foreign monopolist chooses advertising as well as output. On the positive side it is shown that under certain circumstances a tariff will induce a fall in the domestic consumer price of the import. On the normative side the paper demonstrates that an import subsidy can be optimal under two different specifications of the welfare function.
Keywords: Tariff policy; Monopolies; Advertising